JUMLAH KOSAKATA PADA ANAK BERDWIBAHASA DI USIA 16 – 24 BULAN - Selene H. U. Siregar; Mayke Sugianto Tedjasaputra; Luh Surini Yulia Savitri (MANASA, 2012)
There remains controversies about the impact of bilingualism to a child’s languagedevelopment. This research aimed to identify the vocabulary information a child could afford in each language since it is the central measurement of children’s progress in language development. The vocabulary size that has been found in bilingual children ages 16 – 24 months vary between 11 to 182 in Bahasa, and between 5 to 672 in English. Most subjects have higher scores in Bahasa in the category of “nick name of people around”, and in the English language the higher score lies within the category of “vehicles”.